2015
DOI: 10.1097/shk.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Clot Formation Is Associated With Fibrinogen and Platelet Forces in a Cohort of Severely Injured Emergency Department Trauma Patients

Abstract: Introduction Anticoagulation, fibrinogen consumption, fibrinolytic activation, and platelet dysfunction all interact to produce different clot formation responses after trauma. However, the relative contributions of these coagulation components to overall clot formation remains poorly defined. We examined for sources of heterogeneity in clot formation responses after trauma. Methods Blood was sampled in the Emergency Department from patients meeting trauma team activation criteria at an urban trauma center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…The earliest documented change in clot formation in trauma patients is a reduction of clot strength or elastic modulus when measured using viscoelastic methods [3, 42]. Our previous work suggests a similar reduction in elastic and storage modulus of fibrin clot when fibrinogen was exposed to HOCl in vitro [15].…”
Section: Discussionmentioning
confidence: 99%
“…The earliest documented change in clot formation in trauma patients is a reduction of clot strength or elastic modulus when measured using viscoelastic methods [3, 42]. Our previous work suggests a similar reduction in elastic and storage modulus of fibrin clot when fibrinogen was exposed to HOCl in vitro [15].…”
Section: Discussionmentioning
confidence: 99%
“…Viscoelastic haemostatic assays measures which are used to diagnose trauma coagulopathy vary but can be broadly summarised by three main changes: prolongation of clot formation, reduction in clot strength and increase in fibrinolysis. The most common abnormalities include: reduction in A and MCF (ROTEM) (Tauber et al , ; Wooley et al , ; Meyer et al , ) and reduction in MA (TEG) (Meyer et al , ; White et al , ) – all measures of clot strength, and low clot strength is viewed as an important marker, suggesting higher bleeding risk. However, no consensus value is yet agreed – for example Davenport et al () used an EXTEM A5 of ≤35 mm as diagnostic of trauma coagulopathy whereas Hagemo et al () used ≤40 mm.…”
Section: Traumamentioning
confidence: 99%
“…Several studies have indicated that fibrinogen acts as a compensatory mechanism for platelet dysfunction and coagulopathy following severe injury. 13, 2022 In turn, this could also enhance VTE risk in our patient population. Fibrinogen significantly contributes to clot strength, ranging from 23% in healthy individuals 9, 10 to over 40% in trauma patients.…”
Section: Discussionmentioning
confidence: 91%